2005
DOI: 10.1111/j.1365-2222.2005.02194.x
|View full text |Cite
|
Sign up to set email alerts
|

Airway inflammation in nasal polyposis: immunopathological aspects of relation to asthma

Abstract: Our results demonstrate that infiltration of inflammatory cells in the nasal and the lower airways do not remarkably differ between patients with NP alone who has no evidence of BHR and asthmatic patients with NP. However, patients with SPT-ve NP reveal more intense eosinophilic inflammation in the entire respiratory mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 23 publications
5
27
0
Order By: Relevance
“…1,2 As has been described before in European and US studies, histology would reveal prominent edema formation and tissue eosinophilia in the vast majority of polyp specimens, the latter being even more pronounced in patients with concomitant asthma, aspirin sensitivity, or both. 3,4 CRSwNP in white subjects has consistently showed a T H 2 polarization with high IL-5 and IgE concentrations and low levels of TGF-b1. 1 Of note, NPs in patients with cystic fibrosis show edema formation and matrix disruption also but display a prominent neutrophilic instead of eosinophilic inflammation and a significantly lower tissue eosinophil cationic protein (ECP) concentration compared with NPs from patients with CRSwNP, suggesting that edema formation might not necessarily be dependent on tissue eosinophils and their activation.…”
mentioning
confidence: 97%
“…1,2 As has been described before in European and US studies, histology would reveal prominent edema formation and tissue eosinophilia in the vast majority of polyp specimens, the latter being even more pronounced in patients with concomitant asthma, aspirin sensitivity, or both. 3,4 CRSwNP in white subjects has consistently showed a T H 2 polarization with high IL-5 and IgE concentrations and low levels of TGF-b1. 1 Of note, NPs in patients with cystic fibrosis show edema formation and matrix disruption also but display a prominent neutrophilic instead of eosinophilic inflammation and a significantly lower tissue eosinophil cationic protein (ECP) concentration compared with NPs from patients with CRSwNP, suggesting that edema formation might not necessarily be dependent on tissue eosinophils and their activation.…”
mentioning
confidence: 97%
“…In this study, we concomitantly used the oral and the nasal exhaled breath condensate collection to explore the entire upper airway system. The hypothesis that upper airways inflammation can propagate to lower airways in NP has been recently predicted [5]. Lamblin and colleagues described bronchial changes in subjects with NP [6], and subsequent studies confirmed the presence of lower inflammation in NP [27].…”
Section: Discussionmentioning
confidence: 96%
“…Several pro-infiammatory cytokines, such as IL-4 and IL-5 have been implicated in inducing eosinophils production, eliciting tissue damage and finally promoting airway remodelling in NP [4]. It has been recently proposed that nasal polyposis can propagate from upper to lower airways [5]; however, mechanisms binding upper and lower airway inflammation in NP remain poorly understood. Two theories are mainly accepted and include an activation of nasal reflexes, or pulmonary aspiration of nasal contents [6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been well documented that BHR is associated with increased numbers of eosinophils and mast cells in the bronchial airway [18]. A previous study also demonstrated that activated mast cells may play an essential role in the development of BHR in children with chronic asthma, which may be dependent on tryptase-induced upregulation of bronchial smooth muscle tone [19].…”
Section: Discussionmentioning
confidence: 99%